Critical overview of Peracetic acid-based advanced oxidation processes: Evolution, fundamentals and water treatment applications - Yongbo Yu; Jiaxin Yu; Haochen Zhang; Yongchao Mu; Yanjun Xin; Bin Zhang; Jun Ma (Chemical Engineering Journal, 2026)

A double-key responsive TDNs-HC/Cas13a DNA circuit for free-amplified detection and precise imaging of miRNAs in living cell - Shixiu Xiao; Yuying Liang; Yihan Zhang; Longjin Liang; Bin Xu; Xiaomei Mu; Shulin Zhao; Jianniao Tian (Analytica Chimica Acta, 2026)

Multi-response calibration and validation of a DEM for wet Mactra veneriformis–mudflat sediment mixtures during mechanised harvesting - Hangqi Li; Gang Mu; Bin Xu; Guangcong Chen; Guochen Zhang; Xiuchen Li (Biosystems Engineering, 2026)

Preparation and evaluation of silicate stabilized FeS nanoslurry for in-situ remediation of hexavalent chromium - Ning-Ning Xing; Hong-Ling Zhang; Pan-Pan Mu; Hui Jiang; Hong-Bin Xu (Chemical Engineering Journal, 2026)

Efficient fractionation of reed biomass by inorganic salt-driven seawater/ethanolamine pretreatment for fermentable sugars and N-containing lignin - Hao Tong; Meizhen Jiao; Bo Mu; Bin Li; Shihao Su; Yehan Tao; Jinwen Hu; Jian Du; Jie Lu; Chenglong Fu; Haisong Wang (Chemical Engineering Journal, 2026)

Axial oxygen–coordinated niobium single-atom catalyst enables durable bifunctional oxygen reduction/evolution electrocatalysis in zinc–air batteries - Xueyan Lin; Ngoc Thanh Ngan Thai; Yuwei Zhu; Haiyan Tan; Rishav Baranwal; Linqin Mu; Arunachala Mada Kannan; Jingyue Liu; Bin Wang; Zhaoyang Fan (Chemical Engineering Journal, 2026)

Hydrodynamic characteristics of a partitioned recirculating aquaculture pond - Yuxin Liu; Jun Zhang; Shouqi Cao; Di Mu; Xingguo Liu; Bin Wang; Qian Yang; Yusheng Sun (Aquacultural Engineering, 2026)

A dual colorimetric and fluorescent sensor for non-enzymatic glucose detection via catalytic reaction with o-phenylenediamine mediated by carbon dot-decorated Fe3O4 nanoparticles - Wei-Bin Tseng; Wei-Kai Tsai; Ming-Mu Hsieh; Chi-Yu Lu; Po-Chiao Lin; Wei-Lung Tseng (Analytica Chimica Acta, 2026)

Coupled atmosphere-ocean data assimilation for enhanced medium-range prediction of the North Atlantic Oscillation - Bin Mu; Zijun Zhao; Shijin Yuan; Bo Qin; Guokun Dai (Science China Earth Sciences, 2026)

Short-term and lagged effects of ambient air pollution on emergency visits for cardiovascular diseases modified by meteorological factors - Hong Mu; Yufeng Shi; Jiexin Liu; Zhicheng Hu; Xia Wang; Yue Wang; Bin Xu; Rongshan Wu; Jian Xu (International Journal of Hygiene and Environmental Health, 2026)

Enabling long-cycle-life high-voltage calcium metal batteries with fluorinated alkoxyborate-based CaNa hybrid electrolytes - Xinyue Li; Shuangshuang Cui; Bin Chen; Xiaoke Mu; Dechen Zeng; Hongkun Wang; Yang Wang; Bo Peng; Tianyu Zheng; Dianxing Ju; Aobing Du; Zhenyou Li; et al. (Chemical Engineering Journal, 2026)

A Multi-View Sequence Fusion Network for Improving Tropical Cyclone Intensity Estimation - Shijin Yuan; Guansong Wang; Yake Zhang; Bin Mu; Feifan Zhou (Journal of Meteorological Research, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Interactions between nocturnal ozone enhancement and daytime ozone pollution in Guangxi, South China - Yijun Mu; Shanshan Wang; Sanbao Zhang; Jingying Mao; Ruibin Xue; Chuanqi Gu; Jiaqi Liu; Shuyao Xiang; Bin Zhou (Journal of Environmental Sciences, 2026)

MeJA regulates plant root growth, development and phosphorus uptake to adapt to low phosphorus stress - Xinxin Wei; Bin Qiao; Siyao Zhang; Junjie Cui; Rongrong Zhang; Tingting Mu; Guobin Zhang (Plant Science, 2026)

Application of microgels as fat replacers and polyphenol carriers in cheddar cheese - Shanan Chen; Guohua Hou; Qianru Liu; Yifan Zhang; Zhenmin Liu; Haibo Mu; Bin Liu; Xing Li; Zijian Wu; Wen Zhang; Xilong Zhou; Xiangyu Liu; et al. (Food Hydrocolloids, 2026)

A Deep Learning–Based Bias Correction Model for Tropical Cyclone Track and Intensity towards Forecasting of the TianXing Large Weather Model - Shijin Yuan; Xingzhou Wang; Bin Mu; Guansong Wang; Zeyi Niu; Hao Li (Advances in Atmospheric Sciences, 2026)

Sustainable synthesis of phosphate/silicate/biochar composites derived from oil shale semi-coke waste for efficient adsorption and passivation of heavy metals - Dandan Wang; Bin Mu; Feng Zhao; Yan Liu; Yongfeng Zhu; Aiqin Wang (Journal of Environmental Chemical Engineering, 2026)

Recycling acid-leaching clay wastewater to synthesize bimetallic metal-organic frameworks for efficient removal of Pb2+ and UO22+ - Mingcai Ma; Bin Mu; Jiang Xu; Yushen Lu; Aiqin Wang (Journal of Environmental Sciences, 2026)

Carbon dots anchored onto biosynthesized CeO2/attapulgite with enhance antioxidant and light-driven antibacterial activities for food packaging - Wenting Gao; Bin Mu; Fangfang Yang; Yu Tang; Zhihe Luo; Aiqin Wang (Chemical Engineering Journal, 2026)

Regulation of photosynthesis by exogenous MeJA under phosphorus deficiency: a review - Siyao Zhang; Xinxin Wei; Bin Qiao; Junjie Cui; Rongrong Zhang; Tingting Mu; Guobin Zhang (Plant Cell Reports, 2026)

Improving S2S Precipitation Forecast over China via a Deep Learning Model with Multi-Sphere Causality-Linked Predictors - Bin Mu; Hao Guo; Shijin Yuan; Yuxuan Chen; Yuehan Cui; Yanjun Huang (Journal of Meteorological Research, 2026)

Impacts on the maximum lateral deflection and adjacent shield tunnels from the ground stiffness of an excavation - Fan-Yan Meng; Bo Hu; Mu-Chun Liu; Bin-Chen Benson Hsiung; Muhammad Dwiyanto Agung Prakasa (Tunnelling and Underground Space Technology, 2026)

Asymmetric nanochannels for high sensitive detection of AFB1 - Xinrui Xu; Lingxiao Liu; Qianyu Yang; Bin Du; Bing Liu; Xihui Mu; Zhaoyang Tong (Chemical Engineering Journal, 2026)

Revealing dissolution process and mechanism of montmorillonite by two stereoisomers of malic acids and its effect on the Cr(III) retention properties: Insights from DFT simulations and experimental studies - Jingjie Yang; Li Zeng; Yong Wang; Song Liu; Aiqin Wang; Liang Bian; Temirlan Arslanov; Bin Mu; Hailiang Dong; Peng Liu; Xiaobin Gu (Chemical Engineering Journal, 2026)

Optimized Design and Experimental Evaluation of a Vibratory Screening Unit for Mactra veneriformis Harvesting on Intertidal Mudflats Based on the Discrete Element Method - Bin Xu; Shuyuan Liang; Yuzhong Lou; Jixuan Zhao; Hangqi Li; Yizhi Chang; Hao Wu; Guangcong Chen; Gang Mu (Fishes, 2025)
To enhance shell–mud separation and overall harvesting efficiency for Mactra veneriformis under intertidal mudflat conditions, a vibratory harvesting device driven by a crank–rocker mechanism that produces approximately rectilinear simple-harmonic motion was developed. Dynamic analysis of clam motion on the screen deck identified vibration amplitude, vibration frequency, excitation direction angle, and screen deck inclination angle as key determinants of screening performance. Single-factor tests, a Plackett–Burman design, a steepest-ascent experiment, and response surface methodology (RSM) optimization were conducted. Their influences on forward travel speed ranked as follows: screen deck inclination angle > excitation direction angle > vibration amplitude > vibration frequency. The optimized settings were vibration amplitude of 8.5 mm, excitation direction angle of 45°, screen deck inclination angle of 11°, and vibration frequency of 10 Hz. Intertidal mudflat trials yielded a harvesting efficiency of 342 kg/h and a clam breakage rate of 4.6%, meeting the design targets. After harvesting, the shear strength of the mudflat decreased, with disturbance mainly confined to the surface layer, thereby meeting the low-disturbance requirement and enabling ecologically friendly harvesting. These results provide a basis for the design and optimization of M. veneriformis harvesting machinery.

Aerodynamic performance degradation of offshore wind turbine blades under icing with varying angles of attack - Zhongqiu Mu; Guizhong Tian; Xiaoming Feng; Senlin Mu; Fanting Kong; Bin Zhang; Xiangyi Meng (Ocean Engineering, 2025)

Ore-forming process and fluid development at Nanpo Au deposit, Luang Prabang-Loei Belt (NW Laos): Evidence from H-O-S-Pb isotopes and inclusions - Wei Wang; Hui Li; Jie Gan; Fuhao Xiong; Yu Gan; Bin Wang; Junqing Mu; Huan Liu (Journal of Geochemical Exploration, 2025)

Construction of smartphone-assisted electrochemical molecularly imprinted sensor based on magnetic MOF@COF as a novel platform for portable and sensitive detection of staphylococcal enterotoxin B - Wei Hu; Minghao Ma; Bin Du; Yikan Zhao; Jiang Wang; Bing Liu; Xihui Mu; Zhangyan Hu; Zhihao Yi; Zhaoyang Tong (Journal of Environmental Chemical Engineering, 2025)

The reactive oxygen species-induced small RNA CsrO promotes the survival of Cronobacter sakazakii in macrophages and systemic infection within the host - Xiaoya Li; Di Huang; Ruiying Liu; Qiyue Zhang; Xinyuan Yang; Jiake Wang; Min Wang; Qian Wang; Jianwei Mu; Xintong Chen; Miaomiao Liu; Sijia Liu; et al. (Food Research International, 2025)

Morphology of root systems and tensile properties of individual roots across various soil types and layer thicknesses induced by bedrock weathering - Bin-bin Guo; Qing-yi Mu; Yan-jun Shen; Anthony Kwan Leung; Jian-bing Peng (CATENA, 2025)

MicroRNA-451: A multifaceted regulator in cerebral and cardiac ischemia-reperfusion injury - from molecular mechanisms to therapeutic potential - Fei-xiang Wang; Zu-an Shi; Zi-hang Yu; Bin Lu; Guo Mu (Molecular Biology Reports, 2025)

Molecular hydrogen as a novel regulator of cellular pyroptosis: mechanistic insights and therapeutic implications - Yong Ye; Zi-hang Yu; Liang Nie; Bin Lu; Guo Mu (Molecular Biology Reports, 2025)

Enhanced dispersion of mixed-dimensional palygorskite clay via high-pressure homogenization and its synergistic reinforcement in chitosan composites - Yushen Lu; Bin Mu; Yuru Kang; Wenting Gao; Aiqin Wang (Applied Clay Science, 2025)

Revolutionizing toxicological risk assessment: integrative advances in new approach methodologies (NAMs) and precision toxicology - Qiu-Shuang Sheng; Bin Liu; Xiao Wang; Lei Hua; Shou-Cheng Zhao; Xiao-Zhong Sun; Mu-Yang Li; Xiang-Yu Zhang; Jia-Xu Wang; Pei-Li Hu (Archives of Toxicology, 2025)

Mapping urban ultrafine particle exposure in Guangzhou, China: Development of a high-resolution land-use regression framework for megacity - Qing-Guo Zeng; Qi-Zhen Wu; Bin Zhao; Mu-Wu Xu; Yun Zhu; Shi-Cheng Long; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Research, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

Innovative flood prediction modeling: Enhancing efficiency for large-scale simulations and analyzing responses to diverse impacting factors - Junhui Wang; Jingming Hou; Shaowu Li; Bin Lu; Yuru Yan; Yan Mu (Journal of Hydrology, 2025)

Urban-rural inequality in lung cancer risk from indoor air pollution: Prolonged indoor time amplifies the risks of solid fuel use - Ruimin Yang; Xinlin Mu; Guilian Wang; Deliang Tang; Bin Wang; Zhiwen Li; Haidong Kan; Nan Lin; Shu Tao (Journal of Environmental Management, 2025)

Preparation of mesoporous carbon/clay composite adsorbent based on the mixed-dimension attapulgite: Dye adsorption, mechanism and molecular dynamics calculations - Shuo Wang; Yuan Zhang; ChengHui Lan; ChaoXi Mu; JianGuo Liu; MengYao Wang; Bin Mu (Journal of Environmental Chemical Engineering, 2025)

Spirulina-derived atomically dispersed Fe–N4 sites on g-C3N4 for efficient CO2 photoreduction - Haoxian Wang; Junjie Wang; Jin Xu; Jingkai Lin; Zhongshuai Zhu; Yazi Liu; Feihu Mu; Bin Huang; Fei Yu; Chenmin Xu; Shaogui Yang; Huan He; et al. (Chemical Engineering Journal, 2025)

Assessment of Tropical Cyclone Disaster Damage Based on Learnable Inter-City Interaction GNN - Shijin Yuan; Laiyu Yang; Bin Mu; Bo Qin; Yanjun Huang (Journal of Meteorological Research, 2025)

An Interpretable NAO Daily Prediction Model Considering Weighted Causal Effects of Physical Processes - Shijin Yuan; Haoyu Wu; Bin Mu; Yuehan Cui; Bo Qin; Hao Li (Journal of Meteorological Research, 2025)

Design and testing of the clam vibration harvester's V-shaped double-spiral harvesting roller brush based on DEM-MBD - Li Hangqi; Mu Gang; Li Xiuchen; Wu Hao; Xu Bin; Liu Fawei; Sun Zhenyin; Zhang Qian; Zhang Hanbing; Xin Mingjin; Zhang Guochen (Aquacultural Engineering, 2025)

Study on the evolution law of transcritical CO2 double-pipe freezing temperature field in ultra-low temperature strata - Xiu-ling Liang; Bin Wang; Zi-hao Zhang; Yan-hu Mu; Ren-cai Jin (Applied Geophysics, 2025)

Developing Intelligent Earth System Models : An AI scheme of K-profile parameterization and stable coupling into CESM with FTA - Bin Mu; Kang Yang; Bo Qin; Hao Li; Shijin Yuan (Ocean Modelling, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Impact of marine chlorine emissions on secondary organic aerosols in North China Plain - Zhaoqi Gao; Lin Li; Zhou Liu; Jiangshan Mu; Zhuyi Wang; Bin Luo; Jingzhu Zhang; Shuting Tang; Hongliang Zhang; Jianlin Hu; Xuan Wang; Xuehua Zhou; et al. (Environmental Pollution, 2025)

Mechanical Characterization and Dual-Layer Discrete Element Modeling of Mactra veneriformis - Bin Xu; Yazhou Yang; Hangqi Li; Guangcong Chen; Yizhi Chang; Feihong Guo; Hao Wu; Jixuan Zhao; Zijing Liu; Guochen Zhang; Xiuchen Li; Hanbing Zhang; et al. (Fishes, 2025)
The discrete element model of Mactra veneriformis currently employs an oversimplified multi-sphere approach using EDEM’s Hertz–Mindlin model, assuming uniform shell–flesh mechanical properties. This study developed an advanced dual-layer flexible bonding model through comprehensive biomechanical testing. Mechanical properties and shell morphology were experimentally characterized to inform model development. Parameter optimization combined free-fall experiments with Plackett–Burman screening, steepest ascent method, and Box–Behnken RSM, yielding optimal contact parameters: flesh–flesh stiffness (X1) = 3.64 × 1011 N/m3, shell–flesh interface (X3) = 1.48×1013 N/m3, shell–shell tangential stiffness (X6) = 3.23 × 1012 N/m3, and normal strength (X7) = 8.35 × 106 Pa. Validation showed only 4.89% deviation between simulated and actual drop tests, with hydraulic impact tests confirming excellent model accuracy. The developed model accurately predicts mechanical behavior and shell fracture patterns during harvesting operations. This research provides a validated numerical tool for optimizing clam cultivation and harvesting equipment design, offering significant potential to reduce shell damage while improving harvesting efficiency in bivalve aquaculture systems.

Biogeography and Niche Evolution of Odorrana schmackeri Complex in Southern China - Shize Li; Bin Wang; Jing Liu; Haijun Su; Gang Wei; Lang Mu; Tuo Shen; Zhitong Lyu; Yingyong Wang; Houqiang Xu (Journal of Biogeography, 2025)
Aim The Odorrana schmackeri complex (OSC), widely distributed across southern China, presents intriguing mysteries regarding its diversification dynamics. Resolving these evolutionary enigmas would establish a crucial foundation for understanding biogeographic evolution in this topographically complex region. Therefore, we integrated phylogenetic, demographic, and ecological niche analyses to elucidate the roles of ancient tectonism, Quaternary climatic fluctuations, and niche evolution in shaping its diversification and distribution. Location Southern China. Methods Using two mitochondrial and eight nuclear genes, we reconstructed phylogenetic relationships, estimated divergence times and assessed population dynamics. Ecological niche models (ENMs) were optimised via the ‘Kuenm’ package, and niche overlap, equivalency, and similarity were quantified using the ‘ecospat’ R package. Acestral niche and climatic tolerances reconstruction were used in the ‘phyloclim’ package. Results The OSC comprises nine species and originated from a mid‐Miocene ancestor (~12.55 Ma). Mitochondrial phylogeny resolved four deeply divergent clades, while nuclear gene phylogeny revealed incomplete lineage sorting (ILS) and historical gene flow (STRUCTURE, K = 7; JML, p > 0.05). Post‐last glacial maximum (LGM) expansions (~0.02 Ma) facilitated secondary contact in sympatric zones, where niche conservatism dominated between sister species. Ancestral niche reconstruction identified precipitation variables as key drivers of early divergence, while thermal tolerances evolved conservatively. The results indicated that Miocene uplift of the Qinghai‐Tibet Plateau (~12.55–8.70 Ma) promoted southward expansion, while Pliocene‐Pleistocene (~5.58–2.40 Ma) river reorganisations fragmented and later connected populations. Main Conclusions The OSC's diversification reflects the interplay between Miocene–Pliocene tectonism and Quaternary climatic cycles. While ancestral niche divergence along precipitation gradients initiated speciation, post‐LGM sympatry favoured conservatism in thermal microhabitats. Combining multilocus phylogenetics, demographic inference, and niche modelling resolves the rapid‐radiating models in the frog complex and highlights the dynamic roles of landscape features in shaping biogeographic patterns of them.

EAAC-S2S: East Asian Atmospheric Circulation S2S Forecasting with a Deep Learning Model Considering Multi-Sphere Coupling - Bin Mu; Yuxuan Chen; Shijin Yuan; Bo Qin; Zhenchen Liu (Advances in Atmospheric Sciences, 2025)

DEM-DDM study on the humidification uniformity of brown rice in a pan coater - Xiangyi Meng; Yadong Zhu; Zhongqiu Mu; Guizhong Tian; Xiaoming Feng; Bin Zhang; Yongsheng Pei; Yifan Lu (Biosystems Engineering, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Large-scale interviews and plot-based data reveal declining yields of the prized matsutake mushrooms in the major producing areas of China - Yingfeng Bi; Bin Liu; Guangli Chen; Ti Bu; Pengwan Zhang; Qinghong Zhou; Liqin Mu; Yao Fu; Yinxian Shi; Xuefei Yang; Deli Zhai (Journal of Environmental Management, 2025)

Polymer-derived C-Sn/SnO2@rGO heterostructures with dual assistance of gallic acid for high-performance lithium-ion batteries - Guanwen Wang; Baoyi Mu; Ke Cao; Chunlei Chi; Chuanqing Wang; Chao Huangfu; Fan Feng; Bin Qi; Qiushi Miao; Xinhou Yang; Zheng Liu; Tong Wei; et al. (Chemical Engineering Journal, 2025)

Downregulation of HSPB1 and MGST1 Promotes Ferroptosis and Impacts Immune Infiltration in Diabetic Cardiomyopathy - Yaoli Xie; Bin Liang; Zhijun Meng; Rui Guo; Caihong Liu; Yi Yuan; Wei Mu; Yajing Wang; Jimin Cao (Cardiovascular Toxicology, 2025)

Effect of on stereoisomers of lactic acids on microbially-mediated reductive dissolution of clay minerals: Insights from DFT and experimental studies - Jingjie Yang; Liang Bian; Aiqin Wang; Xiaofeng Zhao; Jianan Nie; Temirlan Arslanov; Bin Mu; Hailiang Dong; Mianxin Song; Li Zeng; Peng Liu; Xiaobin Gu (Applied Clay Science, 2025)

Diversity and dynamics of microbial communities during spontaneous fermentation of different cultivars of apples from China and their relationship with the volatile components in the cider - Jingyi Zhou; Xinyi Wang; Yonghao Cao; Yichao Cheng; Wenchao Li; Haibin Mu; Yanying Liang; Bin Tian; Xixi Zhao; Yuyang Song (Food Research International, 2025)

Targeted mutagenesis and functional marker development of two Bna.TAC1s conferring novel rapeseed germplasm with compact architecture - Bin Feng; Yu Wang; Xiaolong Zhang; Tingting Mu; Biaoming Zhang; Yan Li; Haitao Zhang; Wei Hua; Wenya Yuan; Haitao Li (Theoretical and Applied Genetics, 2025)

Association Between Multiple Plasma Toxic Metal and Metalloid Exposures and Hypertension in Elderly Chinese Adults - Yiwen Zhang; Xinyue Mu; Junpu Yu; Aimin Yang; Jingli Yang; Rongjie Wu; Fanhui Luo; Bin Luo; Rentong Chen; Li Ma; Jian He (Biological Trace Element Research, 2025)

A validated criterion for engineering 0D@2D nanocomposite to modulate amyloid peptide self-assembly and fibril disassembly - Qingxue Mu; Guanbin Gao; Zijun Zhang; Bin Zhang; Zhenhua Gu; Xinglin Liu; Liangchong Yu; Lei Shen; Taolei Sun (Chemical Engineering Journal, 2025)

Epigenetic memory as crucial contributing factor in directing the differentiation of human iPSC into pancreatic β-cells in vitro - Abdoulaye Diane; Razik Bin Abdul Mu-U-Min; Heba Hussain Al-Siddiqi (Cell and Tissue Research, 2025)
Impaired insulin secretion contributes to the pathogenesis of type 1 diabetes mellitus through autoimmune destruction of pancreatic β-cells and the pathogenesis of severe forms of type 2 diabetes mellitus through β-cell dedifferentiation and other mechanisms. Replenishment of malfunctioning β-cells via islet transplantation has the potential to induce long-term glycemic control in the body. However, this treatment option cannot widely be implemented in clinical due to healthy islet donor shortage. Emerging β-cell replacement with human-induced pluripotent stem cell (iPSC) provides high remedial therapy hopes. Thus, tremendous progress has been made in developing β-cell differentiation protocols in vitro; however, most of the differentiated iPSC-derived β-cells showed immature phenotypes associated with low efficiency depending on the iPSC lines used, creating a crucial barrier for their clinical implementation. Multiple mechanisms including differences in genetic, cell cycle patterns, and mitochondrial dysfunction underlie the defective differentiation propensity of iPSC into insulin-producing β-cells. Accumulating evidence recently indicated that, following the reprogramming, epigenetic memory inherited from parental cells substantially affects the differentiation capacity of many iPSC lines. Therefore, differences in epigenetic signature are likely to be essential contributing factors influencing the propensity of iPSC differentiation. In this review, we will document the impact of the epigenome on the reprogramming efficacy and differentiation potential of iPSCs and how targeting the epigenetic residual memory could be an additional strategy to improve the differentiation efficiency of existing protocols to generate fully functional hPSC-derived pancreatic β-cells for diabetes therapy and drug screening.

Facile and scalable extrusion fabrication of multifunctional cobalt blue nanocomposite pigments based on natural mixed-dimensional palygorskite clay - Hao Yang; Bin Mu; Lei Wu; Aiqin Wang (Applied Clay Science, 2025)

Thiol-linked hyaluronic acid-mediated encapsulation of RCR-stabilized gold nanoclusters for hyaluronidase sensing and cellular imaging - Manivannan Madhu; Meng-Yuan Tsai; Ming-Mu Hsieh; En-Yu Lin; Wei-Bin Tseng; Chi-Yu Lu; Wei-Lung Tseng (Carbohydrate Polymers, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

USP9X deubiquitinates TRRAP to promote glioblastoma cell proliferation and migration and M2 macrophage polarization - Bin Mu; Jiangpeng Jing; Ruichun Li; Chuankun Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

TianXing: A Linear Complexity Transformer Model with Explicit Attention Decay for Global Weather Forecasting - Shijin Yuan; Guansong Wang; Bin Mu; Feifan Zhou (Advances in Atmospheric Sciences, 2025)

Comparison of primary and secondary metabolites and antioxidant activities by solid-state fermentation of Apios americana Medikus with different fungi - Hee Yul Lee; Hyo Seon Kim; Min Ju Kim; Young Hye Seo; Du Yong Cho; Ji Ho Lee; Ga Young Lee; Jong Bin Jeong; Mu Yeun Jang; Jin Hwan Lee; Jun Lee; Kye Man Cho (Food Chemistry, 2024)

An extension to ensemble forecast of conditional nonlinear optimal perturbation considering nonlinear interaction between initial and model parametric uncertainties - Bin Mu; Zi-Jun Zhao; Shi-Jin Yuan; Xing-Rong Chen; Bo Qin; Guo-Kun Dai (Atmospheric Research, 2024)

A deep learning-based global tropical cyclogenesis prediction model and its interpretability analysis - Bin Mu; Xin Wang; Shijin Yuan; Yuxuan Chen; Guansong Wang; Bo Qin; Guanbo Zhou (Science China Earth Sciences, 2024)

Sub-chronically exposing zebrafish to environmental levels of methomyl induces dysbiosis and dysfunction of the gut microbiota - Mingxiao Li; Xi Chen; Chao Song; Limin Fan; Liping Qiu; Dandan Li; Huimin Xu; Shunlong Meng; Xiyan Mu; Bin Xia; Jun Ling (Environmental Research, 2024)

Copper Nanoparticles Green-Formulated by Curcuma longa Extract Induce Apoptosis via P53 and STAT3 Signaling Pathways in Bladder Carcinoma Cell - Tianjun Xing; Zhu Wang; Xiaojie Hao; Jingjun Mu; Bin Wang (Biological Trace Element Research, 2024)

Production of functional materials from clay minerals and plants for natural resource utilization and sustainable development - Fangzhi Duan; Fangfang Yang; Bin Mu; Yongfeng Zhu; Aiqin Wang (Journal of Cleaner Production, 2024)

Enhancement of non-glycoside phytoestrogens and digestive enzymatic inhibition activity during bioprocessing of isoflavone-enriched soybean leaves by mycelia of Tricholoma matsutake - Hee Yul Lee; Du Yong Cho; Jin Hwan Lee; Jihyun Lee; Jong Bin Jeong; Ji Ho Lee; Ga Young Lee; Mu Yeon Jang; Kye Man Cho (Food Bioscience, 2024)

Use of Tirofiban to Prevent Ischemic Events in Patients with CYP2C19 Loss-of-Function Alleles during Flow Diversion of Intracranial Aneurysm: A Multicenter Cohort Study - Yangyang Zhou; Huibin Kang; Wenqiang Li; Bin Luo; Chao Wang; Ruhang Xie; Yongnan Zhu; Qichen Peng; Yisen Zhang; Jian Liu; Ying Zhang; Shiqing Mu; et al. (Translational Stroke Research, 2024)

Genome-wide analysis of TOPLESS/TOPLESS-RELATED co-repressors and functional characterization of BnaA9.TPL regulating the embryogenesis and leaf morphology in rapeseed - Xiaolong Zhang; Yingying Chen; Hongyu Chen; Chaocheng Guo; Xue Su; Tingting Mu; Bin Feng; Yu Wang; Zhixin Liu; Biaoming Zhang; Yan Li; Haitao Zhang; et al. (Plant Science, 2024)

Ultrasonic disaggregation of mixed-dimensional palygorskite clay for improving ABS resin properties - Jiang Xu; Lei Wu; Bin Mu; Yushen Lu; Qin Wang; Aiqin Wang (Applied Clay Science, 2024)

Hydrothermal-assisted acid-etching of oil shale semi-coke for preparation of mineral/biochar nanocomposites and selective adsorption toward mycotoxins - Feng Zhao; Bin Mu; Yuru Kang; Dandan Wang; Gong Zhu; Aiqin Wang (Journal of Environmental Chemical Engineering, 2024)

An edge feature-based external calibration of monocular camera and LiDAR using in-orbit data - Jiaqian Hu; Bin Song; Jinzhen Mu; Hanxue Zhao; Shuang Li (Advances in Space Research, 2024)

Toward a Learnable Climate Model in the Artificial Intelligence Era - Gang Huang; Ya Wang; Yoo-Geun Ham; Bin Mu; Weichen Tao; Chaoyang Xie (Advances in Atmospheric Sciences, 2024)

Multivariate Upstream Kuroshio Transport (UKT) Prediction and Targeted Observation Sensitive Area Identification of UKT Seasonal Reduction - Bin Mu; Yifan Yang-Hu; Bo Qin; Shijin Yuan (Ocean Modelling, 2024)

Carbon-dot/attapulgite composite sonocatalytic towards efficient indigo-containing wastewater degradation based on the cavitation mechanism - Yu Chen; Yihe Zhang; Jiahe Zhang; Jiale Zhang; Feng Feng; Bin Mu; Na Zhang (Journal of Water Process Engineering, 2024)

Developing intelligent Earth System Models: An AI framework for replacing sub-modules based on incremental learning and its application - Bin Mu; Zi-Jun Zhao; Shi-Jin Yuan; Bo Qin; Guo-Kun Dai; Guan-Bo Zhou (Atmospheric Research, 2024)

Long-term exposure to major constituents of fine particulate matter and neurodegenerative diseases: A population-based survey in the Pearl River Delta Region, China - Qi-Zhen Wu; Hui-Xian Zeng; John Andersson; Anna Oudin; Katja M. Kanninen; Mu-Wu Xu; Shuang-Jian Qin; Qing-Guo Zeng; Bin Zhao; Mei Zheng; Nanxiang Jin; Wei-Chun Chou; et al. (Journal of Hazardous Materials, 2024)

Exposure to flutolanil at environmentally relevant concentrations can induce image and non-image-forming failure of zebrafish larvae through neuro and visual disruptions - Yang Yang; Bin He; Xiyan Mu; Suzhen Qi (Journal of Hazardous Materials, 2024)

IRE1α: from the function to the potential therapeutic target in atherosclerosis - Zheng-Yang Zhou; Li Wu; Yi-Fan Liu; Mu-Yao Tang; Jing-Yi Tang; Ya-Qian Deng; Lei Liu; Bin-Bin Nie; Zi-Kai Zou; Liang Huang (Molecular and Cellular Biochemistry, 2024)

Associations of coal mine dust exposure with arterial stiffness and atherosclerotic cardiovascular disease risk in chinese coal miners - Xuezan Huang; Min Mu; Bin Wang; Haozhe Zhang; Yang Liu; Linling Yu; Min Zhou; Jixuan Ma; Dongming Wang; Weihong Chen (International Archives of Occupational and Environmental Health, 2024)

A deep learning-based bias correction model for Arctic sea ice concentration towards MITgcm - Shijin Yuan; Shichen Zhu; Xiaodan Luo; Bin Mu (Ocean Modelling, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

A ratiometric fluorescence imprinted sensor based on N-CDs and metal–organic frameworks for visual smart detection of malathion - Lidong Yang; Wei Hu; Fubin Pei; Zhiwei Liu; Jiang Wang; Zhaoyang Tong; Xihui Mu; Bin Du; Mingzhu Xia; Fengyun Wang; Bing Liu (Food Chemistry, 2024)

Key function of Kouleothrix in stable formation of filamentous aerobic granular sludge at low superficial gas velocity with polymeric substrates - Xi Chen; Yanzhe Gong; Zhihua Li; Yingming Guo; Hongjiang Zhang; Bin Hu; Wenhao Yang; Yinhuan Cao; Ruihua Mu (Bioresource Technology, 2024)

Scalable, mechanically-robust, fire-resistance MXene/PEDOT:PSS/PBO film for efficient electromagnetic interference shielding and Joule heating performance - Haorui Duan; Chuanshen Wang; Yuxiang Yi; Xiaowei Mu; Hongliang Ding; Zhuyun Bi; Yuan Hu; Bin Yu (Chemical Engineering Journal, 2024)

The Relationships Between Danxia Geoheritages and Regional Tectonics in Southern Sichuan Basin: Implications for the Spatial Distribution of Danxia Landforms in China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yan-Jie Yang; Pengju Li; Liang Qiu; Chao-Bin Xu (Geoheritage, 2024)

Integrated control strategy for dual sludge ages in the high-concentration powder carrier bio-fluidized bed (HPB) technology: Enhancing municipal wastewater treatment efficiency - Chengxian Wang; Xiaoli Chai; Bin Lu; Wei Lu; Hongbo Han; Yue Mu; Qun Gu; Boran Wu (Journal of Environmental Management, 2024)

Unsymmetric design of self-supported sheet electrode: Breaking the tradeoff between electrical conduction and surface wetting for fast energy storage and excellent cycling stability - Bin Zhang; Ze Zhang; Yuefeng Qiu; Zhiheng Wang; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Fuel, 2024)

Composite aerogel incorporating low temperature phase change microcapsules for enhanced thermal insulation - Bin Yan; Min Li; Honglang Lu; Menghan Pi; Jiahao Mu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Longitudinal association of polycyclic aromatic hydrocarbons and genetic risk with lung function - Min Zhou; Shijie Yang; Limin Cao; Wencan Dai; Xiuquan Nie; Ge Mu; Xiaokang Zhang; Bin Wang; Jixuan Ma; Dongming Wang; Tingming Shi; Chaolong Wang; et al. (Environmental Pollution, 2024)

Geochronology and in-situ apatite geochemistry of late Paleoproterozoic A-type granites in the Jiao-Liao-Ji Belt, North China Craton: Implications for petrogenesis and tectonic evolution - Yi-Kang Quan; Mao-Song Mu; De-Bin Yang; Xiang-Yu Yan; An-Qi Wang; Le-Ran Hao; Feng Wang (Geochemistry, 2023)

Mesoporous SiO2 anode armour for lithium oxygen battery - Hailiang Mu; Kun Luo; Yaming Pang; Xiangqun Zhuge; Zhengping Ding; Yurong Ren; Degui Li; Zhihong Luo; Ben Bin Xu; Maryam Bayati; Xiaoteng Liu (Chemical Engineering Journal, 2023)

Assessing the timing and the duration of exposure to air pollution on cardiometabolic biomarkers in patients suspected of coronary artery disease - Kexin Zhu; Zhihui Hou; Conghong Huang; Muwu Xu; Lina Mu; Guan Yu; Joel D. Kaufman; Meng Wang; Bin Lu (Environmental Research, 2023)

Preparation of palygorskite/MIL-88A(Fe) composites for high-efficient removal of Congo red - Wenting Gao; Bin Mu; Yongfeng Zhu; Aiqin Wang (Applied Clay Science, 2023)

A paralleled embedding high-dimensional Bayesian optimization with additive Gaussian kernels for solving CNOP - Shijin Yuan; Yaxuan Liu; Bo Qin; Bin Mu; Kun Zhang (Ocean Modelling, 2023)

Delamination of multilayer Ti3C2T MXene alters its adsorpiton and reduction of heavy metals in water - Yuxuan Zhang; Jun Luo; Biao Feng; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Mu Naushad; Bin Gao; Hongqiang Ren (Environmental Pollution, 2023)

Recent Advances in China on the Predictability of Weather and Climate - Wansuo Duan; Lichao Yang; Mu Mu; Bin Wang; Xueshun Shen; Zhiyong Meng; Ruiqiang Ding (Advances in Atmospheric Sciences, 2023)

An artificial interfacial layer with biomimetic ionic channels towards highly stable Li metal anodes - Yiju Li; Tianshuai Wang; Junjie Chen; Xudong Peng; Minghui Chen; Bin Liu; Yongbiao Mu; Lin Zeng; Tianshou Zhao (Science Bulletin, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Visualizing sub-layer structural transformation in carbonized wood tracheid by Raman mapping - Jingjing Xiong; Binbin Xu; Bin Zhang; Peng Jiang; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Fuel, 2023)

Cross-sectional and longitudinal relationships between ozone exposure and glucose homeostasis: Exploring the role of systemic inflammation and oxidative stress in a general Chinese urban population - Qiyou Tan; Bin Wang; Zi Ye; Ge Mu; Wei Liu; Xiuquan Nie; Linling Yu; Min Zhou; Weihong Chen (Environmental Pollution, 2023)

Dimension shifting based intelligent algorithm framework to solve conditional nonlinear optimal perturbation - Shijin Yuan; Yaxuan Liu; Huazhen Zhang; Bin Mu (Computers & Geosciences, 2023)

Enhancing lead immobilization by biochar: Creation of “surface barrier” via bio-treatment - Huicong Hu; Chao-Sheng Tang; Zhengtao Shen; Xiaohua Pan; Kai Gu; Xiaoliang Fan; Chao Lv; Wen Mu; Bin Shi (Chemosphere, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Experimental study on the explosion destructive ability of magnesium powder/hydrogen hybrids in large space - Xinyu Xiong; Kai Gao; Jie Mu; Changquan Ji; Bin Li; Dan Zhang; Yadong Xu; Lifeng Xie (Process Safety and Environmental Protection, 2023)

Sequence-paleogeography and coal accumulation of the Late Carboniferous – Early Permian paralic successions in western Shandong Province, northern China - Yanwen Shao; Fenghua Zhao; Guangyuan Mu; Bin Sun; Kaihua Liang; Dongdong Wang; Jing Lu; Shimin Ma; Longyi Shao (Marine and Petroleum Geology, 2023)

Recent progress and future prospects on aqueous foams stabilized based on clay minerals - Fangzhi Duan; Yongfeng Zhu; Bin Mu; Aiqin Wang (Applied Clay Science, 2023)

Error Evolutions and Analyses on Joint Effects of SST and SL via Intermediate Coupled Models and Conditional Nonlinear Optimal Perturbation Method - Bin Mu; Xiaoyun Qin; Shijin Yuan; Bo Qin (Journal of Marine Science and Engineering, 2023)
A seasonal predictability barrier has long been noticed in ENSO forecasting with numerical models. Previous studies explored the impact of seasonal optimal initial perturbation evolutions in sea surface temperature anomalies (SSTA) on ENSO forecasting using the intermediate coupled model (ICM) via the conditional nonlinear optimal perturbation (CNOP) method. In this paper, we investigate the joint effects of SSTA and sea level anomalies (SLA) from the perspective of the optimal growth initial error (OGE). After determining the four seasonal OGEs about SSTA and SLA (i.e., SSTA-OGE, SLA-OGE and Joint-OGE), we first demonstrate the patterns, evolutions and the resulting spring predictability barrier (SPB) of the above OGEs. Then, we analyze the mechanism of OGE evolutions and SPB. Finally, we conduct observing system simulation experiments to determine the best (economic) observation network. Our experimental results indicate that the ENSO evolution error induced by SSTA-OGE and Joint-OGE presents season dependency, but SLA-OGE has no impact on ENSO evolution. Moreover, Joint-OGEs induce error evolutions and the SPB with more significant intensity than SSTA-OGEs and SLA-OGEs. From mechanism analyses, the evolutions of SSTA-OGEs are mainly dominated by Bjerknes feedback. Further, the evolution dynamics of Joint-OGEs primarily contain the continuous heating between the upper ocean combined with Bjerknes feedback and thermal diffusion in response to the discharge process. In addition, comprehensive and economical sensitive areas are identified through Joint-OGE, including the central-eastern equatorial Pacific and the western and north-eastern tropical Pacific boundary, which contribute to the ENSO prediction benefits reaching 58.31% on average.

Cleaner preparation of high blueness cobalt blue composite pigments using dolomite and kaolin tailing sand - Hao Yang; Bin Mu; Li Zong; Yingjie Zhu; Aiqin Wang (Journal of Cleaner Production, 2023)

Organic matter accumulation mechanisms in the Wufeng-Longmaxi shales in western Hubei Province, China and paleogeographic implications for the uplift of the Hunan-Hubei Submarine high - Shizhen Li; Zhi Zhou; Haikuan Nie; Mu Liu; Fanyang Meng; Bin Shen; Xiaotao Zhang; Siyu Wei; Zhaodong Xi; Shousong Zhang (International Journal of Coal Geology, 2023)

Effect of CDM3 on co-culture of human-induced pluripotent stem cells with Matrigel-covered polycaprolactone to prepare cardiac patches - Yue Dai; Fan Zhou; Jianwei Zheng; Junsheng Mu; Ping Bo; Bin You (In Vitro Cellular & Developmental Biology - Animal, 2023)

Short-term impacts of air pollution on the platelet-lymphocyte ratio and neutrophil-lymphocyte ratio among urban adults in China - Weihong Qiu; Heng He; Bin Wang; Dongming Wang; Ge Mu; Tao Xu; Min Zhou; Zi Ye; Jixuan Ma; Weihong Chen (Journal of Environmental Sciences, 2023)

Study on derived hydrogen and ignition influencing factors of moist magnesium debris - Xinyu Xiong; Kai Gao; Jie Mu; Changquan Ji; Bin Li; Dan Zhang; Yadong Xu; Lifeng Xie (Fuel, 2023)

Comparison of short-term toxicity of 14 common phycotoxins (alone and in combination) to the survival of brine shrimp Artemia salina - Yuting Zhang; Shanshan Song; Bin Zhang; Yang Zhang; Miao Tian; Ziyi Wu; Huorong Chen; Guangmao Ding; Renyan Liu; Jingli Mu (Acta Oceanologica Sinica, 2023)

Dual functional mesoporous silica colloidal electrolyte for lithium-oxygen batteries - Hailiang Mu; Xiangqun Zhuge; Guogang Ren; Kun Luo; Zhengping Ding; Yurong Ren; Zhihong Luo; Maryam Bayati; Ben Bin Xu; Xiaoteng Liu (Chemical Engineering Journal, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Fractal characterization of pore structure and its influence on CH4 adsorption and seepage capacity of low-rank coals - Guangyuan Mu; Haihai Hou; Jiaqiang Zhang; Yue Tang; Ya-nan Li; Bin Sun; Yong Li; Tim Jones; Yuan Yuan; Longyi Shao (Frontiers of Earth Science, 2022)

New phenolic glycosides from Anemone chinensis Bunge and their antioxidant activity - Zeng-Guang Zhang; Yuan-Yuan Li; Bin Lin; Pei-Pei Guan; Yu Mu; Wen-Jun Qiao; Jing-Sheng Zhang; Xue-Shi Huang; Li Han (Natural Product Research, 2022)

Carbon footprint analysis of straw collection, transportation, and storage system for power generation in China based on emergy evaluation - Yufeng Sun; Bin Yang; Yapeng Wang; Zipeng Zheng; Jinwei Wang; Yaping Yue; Wenlong Mu (Environmental Science and Pollution Research, 2022)

Quantifying soil nitrous oxide emissions in spring freezing-thawing period over different vegetation types in Northeast China - Bin Wu; Chang-cheng Mu; Hui Liu; Ya-kun Xu; Yue Zhang; Jia-shuo Yang; Wen-nian Xu (Journal of Mountain Science, 2022)

Exploring sustainable solutions for the water environment in Chinese and Southeast Asian cities - Pingping Luo; Yong Mu; Shuangtao Wang; Wei Zhu; Binaya Kumar Mishra; Aidi Huo; Meimei Zhou; Jiqiang Lyu; Maochuan Hu; Weili Duan; Bin He; Daniel Nover (Ambio, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Maternal intake of caffeinated products and birth defects: a systematic review and meta-analysis of observational studies - Yan Yue; Wenxing Li; Jun Tang; Yan Zeng; Tao Xiong; Xia Qiu; Jing Shi; Hua Wang; Bin Xia; Lili Luo; Yi Qu; Dezhi Mu (Critical Reviews in Food Science and Nutrition, 2021)

Short-term effects of real-time individual fine particulate matter exposure on lung function: a panel study in Zhuhai, China - Zi Ye; Bin Wang; Ge Mu; Yun Zhou; Weihong Qiu; Shijie Yang; Xing Wang; Zhuang Zhang; Weihong Chen (Environmental Science and Pollution Research, 2021)

Sources of 24-h personal exposure to PM2.5-bound metals: results from a panel study in Wuhan, China - Xing Wang; Bin Wang; Lili Xiao; Xiuqing Cui; Xingzu Cen; Shijie Yang; Ge Mu; Tao Xu; Min Zhou; Weihong Chen (Environmental Science and Pollution Research, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

Kompetitive allele-specific PCR (KASP) genotyping and heterotic group classification of 244 inbred lines in cabbage (Brassica oleracea L. var. capitata) - Zhiyuan Li; Hailong Yu; Xing Li; Bin Zhang; Wenjing Ren; Xiaoping Liu; Zhiyuan Fang; Limei Yang; Mu Zhuang; Honghao Lv; Yangyong Zhang (Euphytica, 2020)

MiR-34a suppresses osteoblast differentiation through glycolysis inhibition by targeting lactate dehydrogenase-A (LDHA) - Mu Hong; Xiao-Bin Zhang; Fei Xiang; Xu Fei; Xue-Lian Ouyang; Xiao-Chun Peng (In Vitro Cellular & Developmental Biology - Animal, 2020)

The Optimal Precursors for ENSO Events Depicted Using the Gradient-definition-based Method in an Intermediate Coupled Model - Bin Mu; Juhui Ren; Shijin Yuan; Rong-Hua Zhang; Lei Chen; Chuan Gao (Advances in Atmospheric Sciences, 2019)

Optimal precursors of double-gyre regime transitions with an adjoint-free method - Shijin Yuan; Mi Li; Qiang Wang; Kun Zhang; Huazhen Zhang; Bin Mu (Journal of Oceanology and Limnology, 2019)

CNOP-P-based parameter sensitivity for double-gyre variation in ROMS with simulated annealing algorithm - Shijin Yuan; Huazhen Zhang; Mi Li; Bin Mu (Journal of Oceanology and Limnology, 2019)

Identifying Typhoon Targeted Observations Sensitive Areas Using the Gradient Definition Based Method - Bin Mu; Juhui Ren; Shijin Yuan; Feifan Zhou (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

RNAi-mediated SLC7A11 knockdown inhibits melanogenesis-related genes expression in rabbit skin fibroblasts - Naisu Yang; Lin Mu; Bohao Zhao; Manman Wang; Shuaishuai Hu; Bin Zhao; Yang Chen; Xinsheng Wu (Journal of Genetics, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

Roles of flotillins in tumors - Xu-xu Liu; Wei-dong Liu; Lei Wang; Bin Zhu; Xiao Shi; Zi-xuan Peng; He-cheng Zhu; Xing-dong Liu; Mei-zuo Zhong; Dan Xie; Mu-sheng Zeng; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2018)

Puerarin-7-O-glucuronide, a water-soluble puerarin metabolite, prevents angiotensin II-induced cardiomyocyte hypertrophy by reducing oxidative stress - Ning Hou; Bin Cai; Cai-Wen Ou; Zhen-Hui Zhang; Xia-Wen Liu; Mu Yuan; Gan-Jian Zhao; Shi-Ming Liu; Long-Gen Xiong; Jian-Dong Luo; Cheng-Feng Luo; Min-Sheng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Efficacy and safety of metformin and sitagliptin based triple antihyperglycemic therapy (STRATEGY): a multicenter, randomized, controlled, non-inferiority clinical trial - Wen Xu; Yiming Mu; Jiajun Zhao; Dalong Zhu; Qiuhe Ji; Zhiguang Zhou; Bin Yao; Anhua Mao; Samuel S. Engel; Bin Zhao; Yan Bi; Longyi Zeng; et al. (Science China Life Sciences, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

CNOP-based sensitive areas identification for tropical cyclone adaptive observations with PCAGA method - Lin-Lin Zhang; Shi-Jin Yuan; Bin Mu; Fei-Fan Zhou (Asia-Pacific Journal of Atmospheric Sciences, 2017)

Water Storage Changes over the Tibetan Plateau Revealed by GRACE Mission - Jinyun Guo; Dapeng Mu; Xin Liu; Haoming Yan; Zhongchang Sun; Bin Guo (Acta Geophysica, 2016)

Measurements of nitrous acid (HONO) in urban area of Shanghai, China - François Bernard; Mathieu Cazaunau; Benoît Grosselin; Bin Zhou; Jun Zheng; Peng Liang; Yujie Zhang; Xingnan Ye; Véronique Daële; Yujing Mu; Renyi Zhang; Jianmin Chen; et al. (Environmental Science and Pollution Research, 2016)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Distributive directions of gully system in Yuanmou Dry-hot Valley - Hongli Mu; Qingchun Deng; Bin Zhang; Fachao Qin; Mingliang Luo; Hui Liu; Shoujiang Liu (Arabian Journal of Geosciences, 2015)

Ectopic WWOX Expression Inhibits Growth of 5637 Bladder Cancer Cell In Vitro and In Vivo - Gang Li; Longfeng Sun; Zhongyi Mu; Yan Huang; Cheng Fu; Bin Hu (Cell Biochemistry and Biophysics, 2015)

Prelog and anti-Prelog stereoselectivity of two ketoreductases from Candida glabrata - Ping Liang; Bin Qin; Mao Mu; Xin Zhang; Xian Jia; Song You (Biotechnology Letters, 2013)

Synthesis of novel isoquinolinone and 1,2-dihydroisoquinoline scaffolds via Ugi reaction and ring opening reaction of furans - Fei Ji; Wen-bin Yi; Mu Sun; Mei-fang Lv; Chun Cai (Molecular Diversity, 2013)

Optimization of the purification methods for recovery of recombinant growth hormone from Paralichthys olivaceus - Xiaonan Zang; Xuecheng Zhang; Xiaosheng Mu; Bin Liu (Journal of Ocean University of China, 2013)

Erratum to: UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

Effects of pH, MES, arabinogalactan-proteins on microspore cultures in white cabbage - Su-xia Yuan; Yan-bin Su; Yu-mei Liu; Zhi-yuan Fang; Li-mei Yang; Mu Zhuang; Yang-yong Zhang; Pei-tian Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

High-level expression of the Penicillium notatum glucose oxidase gene in Pichia pastoris using codon optimization - Zhaowei Gao; Zhuofu Li; Yuhong Zhang; Huoqing Huang; Mu Li; Liwei Zhou; Yunming Tang; Bin Yao; Wei Zhang (Biotechnology Letters, 2012)

New diterpenoids from the roots of Euphorbia ebracteolata Hayata - Bin Deng; Shu-Zhen Mu; Jian-Xin Zhang; Xiao-Jiang Hao (Natural Product Research, 2010)

Immune response to fused core protein of hepatitis C virus and truncated tetanus toxin peptides in mice - Xing-bin Hu; Qiao-hong Yue; Hai-feng Ouyang; Yao-zhen Chen; Xue-qing Xu; Wen Yin; San-hua Wei; Xian-qing Zhang; Shi-jie Mu (Archives of Virology, 2010)

Soil erosion changes over the past five decades in the red soil region of Southern China - Yin Liang; Decheng Li; Xixi Lu; Xuan Yang; Xianzhang Pan; Huan Mu; Deming Shi; Bin Zhang (Journal of Mountain Science, 2010)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Antifungal agent and other constituents from Cynanchum otophyllum - Yi-Bin Zhao; Yue-Mao Shen; Hong-Ping He; Quan-Zhang Mu; Xiao-Jiang Hao (Natural Product Research, 2007)

Molecular cytogenetic characterization of wheat-Thinopyrum ponticum translocations bearing blue-grained gene(s) induced by r-ray - Qi Zheng; Bin Li; Xueyong Zhang; Sumei Mu; Hanping Zhou; Zhensheng Li (Euphytica, 2006)